Phenotypic and genomic analyses of the probiotic Enterococcus casseliflavus SHAMU-QH-02 - Li, Xin-Yu; Liu, Ying; Weng, Sheng-Nan; Chen, Wei; Ju, Gao; Peng, Chuan-Yue; Zhou, Qiang; Yao, Jie; Tang, Wei (Frontiers in Microbiology, 2025)
The past few years have witnessed burgeoning interest in the potential beneficial role of probiotics in multiple fields. This study aimed to explore the probiotic properties and analyze the genomic information of the Enterococcus casseliflavus SHAMU-QH-02 strain, isolated from the human biliary tract. The SHAMU-QH-02 strain was identified using 16S rRNA gene and whole-genome sequencing. The strain exhibited antagonistic activity against most gram-positive cocci, gram-positive bacilli and gram-negative bacilli, especially foodborne pathogens, such as Bacillus cereus, Listeria monocytogenes, Salmonella enteritidis, Vibrio fluvialis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. Antioxidant activity was assessed by ABTS+ scavenging assay and determination of ROS levels. Both the cell-free extract (CFE) and cell-free supernatant (CFS) of the SHAMU-QH-02 strain exhibited strong ABTS+ scavenging ability. Moreover, the CFS demonstrated a higher scavenging ability of ROS. Besides, the SHAMU-QH-02 strain could markedly decrease the production of interleukin-1β (IL-1β) in lipopolysaccharide (LPS)-stimulated RAW264.7 cells, indicating anti-inflammatory activity. Safety assessments indicated no cytotoxicity and susceptibility to 12 common antibiotics. Gastrointestinal stability assessment revealed high tolerance to intestinal pH and bile, yet limited ability to adhere to intestinal epithelial cells. Genomic analysis revealed the presence of hypothetical bacteriocin production genes (n = 2), virulence factor genes (n = 4), and antibiotic resistance genes (n = 23); however, none were located within the eight phage sequences. Importantly, the crude extract obtained using XAD-16HP resin could tolerate extreme pH values, 121°C, and multiple proteases. Taken together, the SHAMU-QH-02 strain exhibits probiotic attributes and presents as a notably promising probiotic candidate, potentially contributing to the food industry, health promotion and disease prevention.